Latihan Sircuit Training Upaya Untuk Meningkatkan Ketepatan Shooting dalampPermainan Sepakkbola - Puriana, Ramadhany Hananto; Pelamonia, Shandy Pieter; Wahyono, Mohammad; Harmono, Bayu Akbar; Maifa, Sitti; Suryansah, Suryansah (Jurnal Porkes, 2022)
Thissresearch wassmotivateddby theeweakness of shooting accuracy in soccerrgames at SSB Gelora Putra delta Sidoarjo, therefore circuit training was carried out so that shooting accuracy in soccer games at SSB Gelora Putra delta Sidoarjo increased. Theepurpose offthis studywwas to determineethe effectoof circuit traininggon increasing shooting accuracy inssoccer gamesaat SSB Gelora Putra Delta Sidoarjo. The designnused innthis studywwas a pretestaand posttestggroup experiment. There is no control variable in this study, so there is no control class. The subjects in this study were SSB Gelora Putra Delta Sidoarjo players, totaling 15 players. Theedata collectionnmethod useddin thissstudy is the testmmethod in measurement. Statistical analysissmethods usedaare normalityntest, homogeneityntest, annt test using SPSS 22. Basednon the resultsnof the calculationnor analysis of theppaired samplesstest data, theet count valueeis 11.225. while theetttable withha significanttlevel of 5% is 1.761 or (t count > t table) which is 11.225 > 1.761. Thus the working hypothesis (H1) which states thattthere issan increaseein circuit traininggon theeshooting accuracyyof SSB Gelora Putra Delta Sidoarjo players, is accepted. The percentage increasenbefore beingngiven treatmentn (pretest) andnafter being givenntreatment (posttest) obtainedna value of 71.32%.